Web-based learning environments supporting socio-scientific decision making - Nicolaidou, Iolie; Michael , Georgia; Kyza, Eleni A.; Papadouris , Nikos; Constantinou , Constantinos P.; Kolias, Vasilis; Asher, Itay; Tabak, Iris (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2023)
In recent years, the rapid progress in science and technology tends to bring about dilemmas on a range of socio-scientific issues. Thus, science education needs to prepare students to deal with such issues in an informed manner. In this paper, four learning environments (LEs) addressing topical socio-scientific issues (i.e. biotechnology, climate change, the impact of fog on human life and nicotine addiction) are presented. The data-rich environments are hosted on the STOCHASMOS web-based teaching and learning platform which offers adjustable scaffolding tools for students’ inquiry. Each of the LEs was designed and implemented in authentic classroom settings of public and private schools of Cyprus’ (n=121) and Israel’s (n=40) secondary education and of Greece’s primary education (n=53). Data collection tools included pre-post tests and observations. Results from the implementation of these LEs are also presented.